2018
DOI: 10.4238/gmr18098
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Association of <i>Six1</i> and <i>Six4</i> gene expression with meat tenderness in Tan sheep

Abstract: Sine oculis-related homeobox 1 (Six1) and 4 (Six4) transcription factors are expressed in developing and adult muscle. These Six homeoproteins are required to activate the fast-type muscle program in the mouse primary myotome. Whether Six1 and Six4 genes have a role in meat tenderness in Tan sheep has not yet been established. To study the characteristics and mechanisms of meat tenderness in Tan sheep, we sampled the musculus triceps muscle, the longest neck muscles, abdominal muscles, gluteus and biceps femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The Chinese Tan sheep is recognized for its meat quality, which is characterized by featured flavors of mutton. However, under stall-feeding conditions, the muscle of Tan sheep contains less IMF, which has became a significant problem (Xu et al, 2018;Gao et al, 2014). Previous studies suggested that the flavor of meat is significantly related to IMF content and FA composition (Qian, 2007;Wood et al, 2008;Wang et al, 2017;Yang et al, 2017;).…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese Tan sheep is recognized for its meat quality, which is characterized by featured flavors of mutton. However, under stall-feeding conditions, the muscle of Tan sheep contains less IMF, which has became a significant problem (Xu et al, 2018;Gao et al, 2014). Previous studies suggested that the flavor of meat is significantly related to IMF content and FA composition (Qian, 2007;Wood et al, 2008;Wang et al, 2017;Yang et al, 2017;).…”
Section: Discussionmentioning
confidence: 99%